Effect of Dibutyltin Dilaurate and Triethanolamine Catalysts on Structure and Properties of Polyimide Foams. Issue 4 (29th March 2019) - Tian, Huafeng; Yao, Yuanyuan; Yin, Duoyuan; Xiong, Weiwen; Xiang, Aimin; Wang, Jianguo
Abstract : A series of rigid polyimide (PI) foams were prepared by the prepolymer method with pyromellitic dianhydride and polyaryl polymethylene isocyanate as the starting materials and dibutyltin dilaurate (DBTDL), and triethanolamine (TEOA) as catalysts. The effect of the two kinds of catalysts on the structure and properties such as molecular structure, cell morphology, density, mechanical properties, thermal properties, and flame retardancy of the resulting foams were characterized in detail. The experimental results showed that the PI foams prepared in this work possessed low density, good mechanical properties, outstanding thermal stability, and excellent flame retardancy. The thermal stability and flame retardancy were improved obviously with the increase of DBTDL content. While with the increase of the content of TEOA, the mechanical strength and apparent density of PI foams increased significantly. Therefore, different structure and performance of PI foams can be prepared by adjusting the content of these two catalysts. J. VINYL ADDIT. TECHNOL., 25:385–395, 2019. © 2019 Society of Plastics Engineers